2006
DOI: 10.3201/10.3201/eid1206.051210
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Prevention and 35 Years of Vector Control in Singapore

Abstract: A vector control program must be based on epidemiologic and entomologic data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
251
0
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(264 citation statements)
references
References 16 publications
5
251
0
8
Order By: Relevance
“…After two decades of successful management in Singapore that relied primarily on an integrated vector-control program, 25 , 26 there has been a resurgence of dengue disease 27 . The recent epidemiology of the disease in Singapore is characterized by a 5–6-y cycle; incidence rates increase within each cycle before declining for 1 or 2 y 28 .…”
Section: Introductionmentioning
confidence: 99%
“…After two decades of successful management in Singapore that relied primarily on an integrated vector-control program, 25 , 26 there has been a resurgence of dengue disease 27 . The recent epidemiology of the disease in Singapore is characterized by a 5–6-y cycle; incidence rates increase within each cycle before declining for 1 or 2 y 28 .…”
Section: Introductionmentioning
confidence: 99%
“…These efforts started in the 1970s and had been shown to be successful for a period of time in Singapore and Cuba (7). However, such efforts were proven to be unsustainable (8) by the explosion of dengue fever cases in recent years (4). A long-term solution to fully eradicate the disease can be achieved by making a safe and effective vaccine, which can simultaneously stimulate protection against all four serotypes.…”
mentioning
confidence: 99%
“…Dengue became hyperendemic in the 1960s, and DHF was a major contributor to childhood deaths. This drove the establishment of an effective vector control program that drastically reduced the Aedes aegypti population from 16% to under 2%, bringing about a 15-year period of low dengue incidence from 1975 to 1990 [23]. When dengue made a resurgence in the 1990s, there was a steady decline in the proportion of patients under 15 years of age and an increase in the proportion of patients above 25 years of age over the years, as well as a trend toward the acquisition of dengue outside the home.…”
Section: Changing Epidemiologymentioning
confidence: 99%
“…A seroprevalence study of adults aged 18-79 years in Singapore comparing the prevalence of anti-dengue IgG antibodies in the population in 2004 and 2010 showed that the age-standardized rates of seroprevalence was significantly lower in 2010 (54 · 4%) compared to 2004 (63 · 1%) [24], implying that a growing proportion of the adult population remained susceptible to dengue virus infections. These findings led the authors to propose that the successful vector control and surveillance program resulted in lowered seroprevalence and herd immunity in the adult population, while the shift in acquisition patterns toward one that was outside of the home (due to better vector elimination in residential versus non-residential sites), resulted in the acquisition of disease at a later stage in life [23].…”
Section: Changing Epidemiologymentioning
confidence: 99%